Analisis Faktor Penyebab Rendahnya Bed Occupancy Rate (Bor) - Angeli Br Surbakti; Selfin Yanti Telaumbanua (Yayasan Literasi Sains Indonesia, 2023)
BOR is an indicator of health services that can be used to determine the level of quality, level of facility utilization and efficiency of health services. The impact of decreasing BOR causes a decrease in economic income for hospitals. The aim is to analyze the factors causing the low percentage of BOR at the Mitra Medika Bondowoso Hospital, at the Makassa Community Lung Health Center, at the Sleman Regional Hospital. The results obtained from the factors causing the low BOR are the lack of facilities owned by hospitals, the shortage of staff which causes officers to have to work extra to carry out other tasks so that the officer's workload increases and services will take longer, Discipline of Health Officers, Analyzing priorities , lack of coordination between registration officers, patient care ward officers, errors when inputting patient information data, supervision activities carried out by each room head. The service rates at the hospital in question are the amount of costs that must be paid by the patient to obtain health services, the policies implemented by the hospital and the competition between each hospital.